EFFECT OF KEGEL EXERCISE ON WOUND HEALING INDEX AFTER COLORECTAL SURGERY: Pharmaceutical Sciences-Nursing - S, NAJAFI DOULATABAD; F, PIRAMI; S, ZABOLI; FAR A, AFRASEYABI (International Journal of Life Science and Pharma Research, 2017)
The most important complications after colorectal surgery is delayed wound healing which use of nonpharmacologic methods to reduce the complications has been considered by researchers. This study was conducted aiming at study on effect of Pelvic-floor muscle (PFM) exercises on Wound Healing Index after colorectal surgery.Materials and methods: this study is a randomized clinical trial; the statistical population under study consisted of all the women patients suffered from benign colorectal diseases referred to Shahid Rajaee Hospital (Gachsaran) and hospital Yasuj Shahid Beheshti. 96 patients were selected via Nonprobability sampling, then were considered in two experimental and control groups in random allocation way. The patients in the intervention group before surgery were trained with pelvic floor muscle exercises. Wound healing data at 3, 7 and 14 days after surgery were collected using REEDA Wound Healing Scale. The collected data were analyze via software SPSS-version 22 using descriptive statistics and inferential tests (T-test, chi-square, Fisher, Kolmogorov-Smirnov, Mann-Whitney) and considering the confidence interval (95%).findings of study indicated that mean of overall score of wound healing in test group at 3, 7 and 14 days after surgery has been 5.2±2.5, 1.7±2.6, 0.2±1.3 which a significant difference was not observed between two groups(p>0.05).with regard to the findings of the present research, Pelvic-floor muscle (PFM) exercise has no effect on wound healing indices after colorectal surgery, thus it requires conducting further research in this context.